2016
DOI: 10.3122/jabfm.2016.01.150349
|View full text |Cite
|
Sign up to set email alerts
|

Family Medicine Research That Provides Compelling, Urgent Data to Improve Patient Care

Abstract: Herein is positive, mixed, and negative news-albeit all useful-on family medicine topics. The time to depression remission can be dramatically reduced. There is compelling evidence on how to improve medication reconciliation. There is a major underestimated determinant of the length of intrauterine device use. Data on the convoluted nature of the International Classification of Diseases, 10th Revision, transition could cause heart sink for doctors. Another article notes how family physicians can improve the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Research has shown that family support can improve the quality of life of patients with alcohol-induced mental disorders, reduce the occurrence of anxiety and depression, reduce the frequency of alcohol consumption, and reduce the occurrence and severity of mental symptoms ( 16 , 17 ). It can also improve patients’ ability to respond to adverse events, timely alleviate psychological crises, and fundamentally achieve the goal of eliminating bad drinking habits ( 18 ). However, there was no report on the effect of family intervention on the relapse rate of alcohol dependence in Chinese patients.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that family support can improve the quality of life of patients with alcohol-induced mental disorders, reduce the occurrence of anxiety and depression, reduce the frequency of alcohol consumption, and reduce the occurrence and severity of mental symptoms ( 16 , 17 ). It can also improve patients’ ability to respond to adverse events, timely alleviate psychological crises, and fundamentally achieve the goal of eliminating bad drinking habits ( 18 ). However, there was no report on the effect of family intervention on the relapse rate of alcohol dependence in Chinese patients.…”
Section: Introductionmentioning
confidence: 99%